2020
DOI: 10.4193/rhin20.189
|View full text |Cite
|
Sign up to set email alerts
|

Anosmia as a presenting symptom of SARS-CoV-2 infection in healthcare workers – A systematic review of the literature, case series, and recommendations for clinical assessment and management

Abstract: Background: Healthcare workers are at the forefront of the ongoing COVID-19 pandemic and are at high risk for both the contraction and subsequent spread of virus. Understanding the role of anosmia as an early symptom of infection may improve monitoring and management of SARS-CoV2 infection. Methodology:We conducted a systematic review of the literature of SARS-CoV2 infection/COVID-19 and anosmia to help inform management of anosmia in healthcare works. We report a case series of healthcare workers, who present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 25 publications
1
65
0
1
Order By: Relevance
“…Aftermath of the first phase of COVID-19 might be especially challenging for Otorhinolaryngology clinics around the globe. There are many studies addressing smell and taste loss in the literature, each reporting different prevalence [19,[30][31][32][33]. A recent meta-analysis reported the prevalence of olfactory dysfunction as 52.73% and gustatory dysfunction as 43.93% [15].…”
Section: Discussionmentioning
confidence: 99%
“…Aftermath of the first phase of COVID-19 might be especially challenging for Otorhinolaryngology clinics around the globe. There are many studies addressing smell and taste loss in the literature, each reporting different prevalence [19,[30][31][32][33]. A recent meta-analysis reported the prevalence of olfactory dysfunction as 52.73% and gustatory dysfunction as 43.93% [15].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly two case studies reports SARS-CoV-2 meningitis/encephalitis (Moriguchi et al, 2020;Ye et al, 2020); however, only one of them had a confirmed positive SARS-CoV-2 RT-PCR test on CSF (Moriguchi et al, 2020). ACE2 is a functional receptor for SARS-CoV-2 (Li et al, 2005) and it is known that ACE2 is expressed in neurons (Troyer et al, 2020), which is interesting in the light of the many reports of anosmia as an early symptom of COVID-19 (Lechner et al, 2020), since SARS-CoV-1 has been suggested to enter the brain trough the olfactory bulb (Netland et al, 2008). Taken together this indicates that SARS-CoV-2 could be neurotrophic entering the brain through the olfactory bulb, leading to an increase in neuropsychiatric symptoms among the patients surviving COVID-19.…”
Section: Potential Biological Mechanisms Of Sars-cov-2 and The Effectmentioning
confidence: 94%
“…108 This has resulted in anosmia to be included in the list of symptoms used in early screening tools for possible COVID-19 in many international bodies. 108…”
Section: What Is the Importance Of Smell Loss In The Diagnosis Of Cmentioning
confidence: 99%